Case Studies In Finance: Managing For Corporate Value Creation - BRUNER, Robert F (McGraw-Hill International, 2007)
Case Studies in Finance links managerial decisions to capital markets and the expectations of investors. At the core of almost all of the cases is a valuation task that requires students to look to financial markets for guidance in resolving the case problem. The focus on value helps managers understand the impact of the firm on the world around it. These cases also invite students to apply modern information technology to the analysis of managerial decisions. The cases may be taught in many different combinations. The eight-part sequence indicated by the table of contents relates to course designs used at the authors' schools. Each part of the casebook suggests a concept module, with a particular orientation.